Reflex control of human locomotion: Existence, features and functions of common interneuronal system induced by multiple sensory inputs in humans - Tsuyoshi Nakajima; Rinaldo A. Mezzarane; Tomoyoshi Komiyama; E. Paul Zehr (Japanese Society of Physical Fitness and Sports Medicine, 2015)
Neural output from the locomotor system for each arm and leg influences the spinal motoneuronal pools directly and indirectly through interneuronal (IN) reflex networks. This review article mainly describes the recent findings concerning the existence, features and functions of common IN systems on spinal reflex pathways induced by multisensory inputs during human locomotion. In particular, we focus on regulation of polysynaptic cutaneous reflex pathways assessed by spatial facilitation. Furthermore, we provide evidence for activation of common presynaptic inhibitory INs that integrate locomotor-related commands and antagonist group Ia inputs. The experimental results are discussed in light of recent advances in motor control in humans and other animals with implications for locomotor rehabilitation.